Outside Front Cover: Volume 2 Issue 2. (29th June 2021) - Sun, Mingyuan; Zhang, Congcong; Chen, Duo; Wang, Jian; Ji, Yanchen; Liang, Na; Gao, Haoyang; Cheng, Shanshan; Liu, Hong
Abstract : Outside front cover image : Just as Nezha's body composed of lotus root silk and meridian can accurately repel shrimp and crabs in the ocean, Sun and co‐workers reported that an all‐graphene FET device assembled of two coupling agents with different functions can also accurately detect mercury ions in the solution phase ultrasensitively and stably. (DOI: https://doi.org/10.1002/smm2.1030 )